2019
DOI: 10.1177/0825859718816073
|View full text |Cite
|
Sign up to set email alerts
|

Observational Pain Assessment Instruments for Use With Nonverbal Patients at the End-of-life: A Systematic Review

Abstract: Purpose: To review studies pertaining to the reliability and validity of observational pain assessment tools for use with nonverbal patients at the end-of-life, a field of research not documented by previous systematic reviews. Methods: Databases (PubMed, Embase, Epistemonikos, the Cochrane Library, and CINAHL) were systematically searched for studies from study inception to February 21, 2016 (update in May 9, 2018). Two independent reviewers screened study titles, abstracts, and full texts according to inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Similar to this finding, Tapp et al, [33] reported that due to the subjective nature of pain, its assessment and management can only be attained when there is effective communication between patients and health care providers. Specifically, effective communication between nurses and patients can result in more effective pain management [34].…”
Section: Discussionsupporting
confidence: 55%
“…Similar to this finding, Tapp et al, [33] reported that due to the subjective nature of pain, its assessment and management can only be attained when there is effective communication between patients and health care providers. Specifically, effective communication between nurses and patients can result in more effective pain management [34].…”
Section: Discussionsupporting
confidence: 55%
“…Of the pain assessment instruments identified, the Critical Care Pain Observation Tool and Behavioural Pain Scale have both been extensively validated in critically ill intubated adult patients (Stites, 2013; Tapp et al, 2019; Varndell, Fry, & Elliott, 2016), yet were infrequently (26.5%) used. While adequate pain relief in the ED is paramount to optimising patient comfort, critically ill patients frequently experience moderate‐to‐severe pain whilst intubated and mechanically ventilated that is often under‐recognised and under‐treated (Batiha, 2014; Clukey, Weyant, Roberts, & Henderson, 2014; Thomas, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to their psychometric properties Goebel et al (2019) found PAINAD to be a reliable and valid tool for pain screening in medical or surgical settings. However, a recent systematic review (Tapp et al 2019) assessing pain assessment tools for non-verbal patients at EoL concluded that more work is needed to improve the scientific basis for testing and recommended a new tool be developed for this population. The EPCA assessment scale was assessed by Morello et al (2007) was found to have good psychometric properties and was included in a 2016 systematic review (Husebo et al 2016).…”
Section: Table 4 Herementioning
confidence: 99%